2021
DOI: 10.1155/2021/8800358
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Novel Immune-Related lncRNA Pair Signature with Prognostic Significance for Kidney Clear Cell Renal Cell Carcinoma

Abstract: Background. Renal cell carcinoma (RCC) is one of the most common aggressive malignant tumors in the urinary system, among which the clear cell renal cell carcinoma (ccRCC) is the most common subtype. The immune-related long noncoding ribonucleic acids (irlncRNAs) which are abundant in immune cells and immune microenvironment (IME) have potential significance in evaluating the prognosis and effects of immunotherapy. The signature based on irlncRNA pairs and independent of the exact expression level seems to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…The immune correlation heatmap showed the distribution of immune cells in different clusters. CD8+ T cells from TIMER, CIBERSORT-ABS, QUANTISEQ, and XCELL had significantly more infiltration in Cluster2 ( Supplementary Table 3 ; Supplementary Figure 1B ) ( 24 ). Several immune checkpoints were significantly higher in Cluster2 than Cluster1, specifically PD1, PD-L1, CTL4, LAG3, and TIM3 ( Figure 2F ).…”
Section: Resultsmentioning
confidence: 99%
“…The immune correlation heatmap showed the distribution of immune cells in different clusters. CD8+ T cells from TIMER, CIBERSORT-ABS, QUANTISEQ, and XCELL had significantly more infiltration in Cluster2 ( Supplementary Table 3 ; Supplementary Figure 1B ) ( 24 ). Several immune checkpoints were significantly higher in Cluster2 than Cluster1, specifically PD1, PD-L1, CTL4, LAG3, and TIM3 ( Figure 2F ).…”
Section: Resultsmentioning
confidence: 99%
“…As a revolutionary therapy, immunotherapy has shown its improvement in prolonging the survival of various malignant tumors, including lung cancer, gastric cancer, bladder cancer, and melanoma. Moreover, some studies illustrated that ICIs could obviously increase the survival of intermediate-or poor- risk metastatic ccRCC patients with fewer adverse reactions (36,37). However, as a common issue for immunotherapies, only limited ccRCC patients could receive therapeutic benefits from ICIs.…”
Section: Discussionmentioning
confidence: 99%
“…Dong et al identified a redox-related lncRNA signature of RCC and the AUC value was 0.82 ( Qi-Dong et al, 2020 ). Sun et al constructed an immune-related lncRNA pair signature of RCC and the AUC value was 0.76 ( Sun et al, 2021 ). In our prognostic model, we constructed a tumorigenesis-related and immune infiltration-related lncRNA signature for predicting the prognosis of RCC, with an AUC value of 0.9.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported several prognostic models for RCC. However, the Area Under Curve (AUC) values were all less than 0.83 (Qi-Dong et al, 2020;Ma et al, 2021;Sun et al, 2021;Yu et al, 2021). Therefore, a more efficient model is urgently needed for predicting the prognosis of RCC.…”
Section: Introductionmentioning
confidence: 99%